Post-Hoc Analysis of a Randomized, Double Blind, Prospective Study at the University of Chicago: Additional Standardizations of Trial Protocol are Needed to Evaluate the Effect of a CXCR1/2 Inhibitor in Islet Allotransplantation. (15th April 2021) - Bachul, Piotr J.; Golab, Karolina; Basto, Lindsay; Zangan, Steven; Pyda, Jordan S.; Perez-Gutierrez, Angelica; Borek, Peter; Wang, Ling-Jia; Tibudan, Martin; Tran, Dong-Kha; Anteby, Roi; Generette, Gabriela S.; et al.
A recent randomized, multicenter trial did not show benefit of a CXCR1/2 receptor inhibitor (Reparixin) when analysis included marginal islet mass (>3, 000 IEQ/kg) for allotransplantation and when immunosuppression regimens were not standardized among participating centers. We present a post-hoc analysis of trial patients from our center at the University of Chicago who received an islet mass of over 5, 000 IEQ/kg and a standardized immunosuppression regimen of anti-thymocyte globulin (ATG) for induction. Twelve islet allotransplantation (ITx) recipients were randomized (2:1) to receive Reparixin ( N = 8) or placebo ( N = 4) in accordance with the multicenter trial protocol. Pancreas and donor characteristics did not differ between Reparixin and placebo groups. Five (62.5%) patients who received Reparixin, compared to none in the placebo group, achieved insulin independence after only one islet infusion and remained insulin-free for over 2 years ( P = 0.08). Following the first ITx with ATG induction, distinct cytokine, chemokine, and miR-375 release profiles were observed for both the Reparixin and placebo groups. After excluding procedures with complications, islet engraftment on post-operative day 75 after a single transplant was higher in the Reparixin group ( n = 7) than in the placebo ( n = 3) group ( P = 0.03) when islet graft function was measured by the ratio of the area under the curve (AUC) for c-peptide to glucose in mixed meal tolerance test (MMTT). Additionally, the rate of engraftment was higher when determined via BETA-2 score instead of MMTT ( P = 0.01). Our analysis suggests that Reparixin may have improved outcomes compared to placebo when sufficient islet mass is transplanted and when standardized immunosuppression with ATG is used for induction. However, further studies are warranted. Investigation of Reparixin and other novel agents under more standardized and optimized conditions would help exclude confounding factors and allow for a more definitive evaluation of their role in improving outcomes in islet transplantation. Clinical trial reg. no. NCT01817959, clinicaltrials.gov